HUBUNGAN AKTIVITAS FISIK DENGAN KEJADIAN RISIKO OBESITAS PADA ANAK USIA SEKOLAH DI SDN GROGOL 02 DEPOK - Fitrianih Azzahra, (2022)
School-age children can be interpreted as children aged 6-12 years where at this age children acquire basic knowledge and skills for the successful adjustment of children in adult life. This study aims to determine the relationship between physical activity and the risk of obesity in school-age children at SDN Grogol 02 Depok. This study used a cross-sectional research design with a sample of 193 respondents using the probability sample method. Analysis of the data used in this study is univariate analysis and bivariate analysis with Chi Square test. The results of this study indicate that there is a relationship between physical activity and the risk of obesity (p value = 0.000). The suggestion from this researcher is that parents can maintain their eating patterns and physical activity habits, and it is also hoped that school-age children can do physical activity with light exercise or other activities. Also regulate the food consumed as an effort to prevent obesity.